Healthy Urban Planning: Meaning of Sustainable Development to Improve the Quality of Human Life in the City - Sulistyarso, Haryo (Faculty of Psychology, Universitas Surabaya, 2007)
Urban planning, as one of the first important process in developing a city, should also ac- commodate ethical dimensions of sustainable development which could promote health and the quali- ty of human life, through a harmonious relation between human and nature. A healthy city should meet the basic needs for all the city’s people, among others promoting a high health status and low levels of disease, a high degree of participation and control by the public over the decisions affecting their lives, health and wellbeing. Other planning policies and qualities of a healthy city are also discussed. Perencanaan kota, sebagai salah satu proses penting pertama dalam mengembangkan se- buah kota, seyogianya juga mengakomodasi dimensi etis pengembangan yang berkelanjutan yang mampu meningkatkan kesehatan dan kualitas hidup manusia, melalui hubungan harmonis antara ma- nusia dan alam. Sebuah kota yang sehat wajib memenuhi kebutuhan dasar seluruh penghuni kota, an- tara lain peningkatan status kesehatan yang tinggi dan langka penyakit, tingkat keperansertaan yang tinggi dan kontrol ketat oleh masyarakat menyangkut putusan yang memengaruhi kehidupan, keseha- tan, dan kesejahteraannya. Didiskusikan pula kebijakan perencanaan dan kualitas kota sehat yang lain.